Standardisasi Mutu Fisik Ekstrak Etanol Daun Pare Hijau (Momordica carantia L.) - Rusmin Rusmin; A.Tenriugi Dg. Pine (Akademi Farmasi Yamasi Makassar, 2020)
Green bitter leaves (Momordica carantia L.) is one of the plants that can be used as medicine for worms, wounds, and ulcers. This study aims to determine the ethanol extract of green bitter leaves (Momordica carantia L.) can meet the quality requirements of nonspecific parameters and specific parameters. Green pare leaf (Momordica carantia L.) dried is extracted with 96% ethanol solvent using maceration method. The extract obtained was tested specifically and nonspecific quality. The results showed that the standardized extract of green bitter leaves (Momordica carantia L.) was 96% ethanol extract with specific and nonspecific parameter values ​​as follows: extract in the form of thick, dark green, distinctively smelling, and tasting bitter; yield is 17.3%: drying losses are 28.39%.